The Effect of Training, Teaching Experience, and Organizational Culture on the Professionalism of State Senior High School Teachers - Hana Maria Uli Lumbanraja (Berugak Baca, 2024)
This study aims to determine how much influence training, teaching experience, and organizational culture have on teacher professionalism in public high schools partially and simultaneously. This research is a quantitative research with ex-post facto research type. The population in this study were all teachers at public high schools in Muara Enim District, totaling 128 people who were taken as respondents (population study). Data collection techniques using questionnaires and documentation studies. Instrument validity test using Expert Judgment and Product Moment Correlation. Instrument reliability test using Cronbach's Alpha. Data analysis techniques using multiple linear regression methods. The results showed that: 1) There is a partial effect of training on teacher professionalism by 8.8%, this is indicated by the tcount value of 2.871> ttable 1.979; significance value of 0.005 <0.05; 2) There is a partial effect of teaching experience on teacher professionalism by 7.1%, this is indicated by the tcount value of 2.269> ttable 1.979; significance value of 0.025 < 0.05; 3) There is a partial influence of school organizational culture on teacher professionalism by 10.1%, this is indicated by the tcount value of 2.603 > ttable 1.979; significance value of 0.010 < 0.05; and 4) Simultaneously there is an influence of training, teaching experience, and school organizational culture on the professionalism of public high school teachers in Muara Enim District by 26.1%, this is indicated by the Fcount value 14.579 > Ftable 2.68 and a significance value of 0.000 < 0.05.